Extrathoracic collaterals to critical segmental arteries after endovascular thoraco-abdominal aneurysm repair. (9th March 2020) - Shijo, Takayuki; Kuratani, Toru; Shimamura, Kazuo; Kin, Keiwa; Masada, Kenta; Goto, Takasumi; Ide, Toru; Takahara, Mitsuyoshi; Sawa, Yoshiki
Abstract: OBJECTIVES: The risk of spinal cord injury after thoraco-abdominal aortic aneurysm repair increases when the segmental arteries (SAs) in the critical segment are sacrificed. Such critical SAs cannot be reconstructed when performing thoracic endovascular aortic repair (TEVAR). We aimed to elucidate extrathoracic collaterals to the critical SAs (T9–L1) that develop after TEVAR. METHODS: Between 2006 and 2018, the critical SAs (T9–L1) of 38 patients were sacrificed during TEVAR. Nineteen of these patients who underwent multidetector row computed tomography 6 months after surgery were included (mean age 60 ± 13 years; 10 male; Crawford extent II:III, 14:5). We retrospectively assessed extrathoracic collaterals to the sacrificed critical SAs. RESULTS: Ninety-four collaterals to the critical SAs were observed, originating from the subclavian (26/94), external iliac (50/94) and internal iliac (18/94) arteries. Twenty-five of the 26 (96%) collaterals from the subclavian artery were from its lateral descending branch, and 19 of the 26 (73%) collaterals fed into T9. Forty-three of the 50 (86%) collaterals from the external iliac artery were from its lateral ascending branch, and 25 of the 50 (50%) collaterals communicated with T11. Patients with a history of left thoracotomy (no collaterals in 6 patients) had fewer collaterals via the lateral descending branch of the left subclavian artery in comparison with the patients without (10 collaterals in 13 patients) ( P = 0.009). CONCLUSIONS: After critical SAs were sacrificed, extrathoracic collaterals developed with certain regularity. Previous left thoracotomy could influence the development of extrathoracic collaterals from the left subclavian artery.